2021
DOI: 10.3390/nano11081993
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Polyaniline Doped with Ag+ or Cu2+ on Carbon Nanotubes for Ethylene Chemical Sensing

Abstract: Multi-walled carbon nanotubes (MWCNTs) are promising materials for chemical gas sensing because of their high electrical and mechanical properties and significant sensitivity to changes in the local environment. However, high-content MWCNT films suffer from the low tunability of the electrical resistance, which is crucial for high chemoresistive sensing performance. This study reports the conjugation of MWCNTs and oligomers of polyaniline (PANI) doped with Ag+ or Cu2+ incorporated into a PVC/polyacrylate. MWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Toxic gas sensing with semiconducting carbon nanotubes (as chemical and biological sensors) has been proposed [ 11 ]. Literature review shows that CNTs revealed good sensitivity to gases such as H 2 , NH 3 , NO 2 , SO 2 , CO, CH 4 , O 2 and H 2 S. The adsorption of substrate molecules on the sidewalls of CNTs alters its electrical properties [ 12 ]. This change in electrical properties can be utilized as output signals in CNTs based sensors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic gas sensing with semiconducting carbon nanotubes (as chemical and biological sensors) has been proposed [ 11 ]. Literature review shows that CNTs revealed good sensitivity to gases such as H 2 , NH 3 , NO 2 , SO 2 , CO, CH 4 , O 2 and H 2 S. The adsorption of substrate molecules on the sidewalls of CNTs alters its electrical properties [ 12 ]. This change in electrical properties can be utilized as output signals in CNTs based sensors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%